Effects of Immediate Aversive Stimulation on Haloperidol-Induced Catalepsy in Rats - Waku, Isabelle; Reimer, Adriano E.; de Oliveira, Amanda R. (Frontiers in Behavioral Neuroscience, 2022)
In animal models, the administration of the dopaminergic D2 antagonist haloperidol affects the nigrostriatal pathway, inducing catalepsy, a state of immobility similar to Parkinson’s disease (PD) bradykinesia and akinesia. In PD, the motor impairments are due to difficulties in selecting and executing motor actions, associated with dopamine loss in basal ganglia and cortical targets. Motor and affective limbic networks seem to be integrated via a striato-nigro-striatal network, therefore, it is not surprising that the motor impairments in PD can be influenced by the patient's emotional state. Indeed, when exposed to aversive stimuli or life-threatening events, immobile patients are capable of performing sudden movements, a phenomenon known as paradoxical kinesia. Thus, the present study investigated the effects of unconditioned and conditioned aversive stimulation on haloperidol-induced catalepsy in rats. First, male Wistar rats received intraperitoneal administration of saline or haloperidol (1 or 2 mg/kg) and were evaluated in the catalepsy bar test to assess the cataleptic state induced by the different doses of haloperidol over time. Next, we evaluated the effects of two types of unconditioned aversive stimuli - 100 lux light (1 and 20 s) or 0.6 mA footshock (1 s) - on the catalepsy. Finally, we evaluated the effects of light conditioned stimuli (Light-CS), previously paired with footshocks, on the cataleptic state. Catalepsy was observed following haloperidol 1 and 2 mg/kg administration. Exposure to footshocks, but not to light, significantly reduced step-down latency during the catalepsy test. Although unconditioned light did not affect catalepsy, paired Light-CS did reduce step-down latency. Here, we have provided evidence of face validity for the study of paradoxical kinesia. In addition to demonstrating that immediate exposure to an aversive stimulus is capable of disrupting the cataleptic state, our findings show that haloperidol-induced catalepsy seems to be differently influenced depending on the modality of aversive stimulation. Our data suggest that the selective recruitment of threat response systems may bypass the dysfunctional motor circuit leading to the activation of alternative routes to drive movement.